Pengembangan Game Edukasi Kata Benda Bahasa Arab Pendahuluan dengan Iterative With Rapid Prototyping - Arief Alamsyah; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Arab language known as one of main language of most people in Middle East and North Africa. Arab language is a language that being used by 25 country and used as Islam Religion believer because Arab language are written and used on Al bible. As known language that being used for Al Qur'an as Islam bible. But because Arab language itself not major language, it will be harder for some people to learn Arab language compared to Indonesia language because of low motivation. Using common gadget like computer or mobile phone and using educational game as media for learning Arabic Language to make user for easier learning about Arabic Language and increase their motivation for Arab learning. Using Iterative With Rapid Prototyping as development method can fix the problem in case there is a problem found during development process. After the game developed and can be implemented, game will be tested using System Usability Scale (SUS) to check if the game system has problem and using Game Experience Questionnaire (GEQ) on core questionnaire module to find out about game experience of user when playing game.